OPTIMASI PRODUKSI SERTA ANALISIS AKTIVITAS ANTIOKSIDAN DAN ANTIMIKROBA SENYAWA EKSOPOLISAKARIDA DARI JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA MEDIA CAIR - Iwan Saskiawan; Misbahul Munir; Suminar S Achmadi (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Pleurotus ostreatus is well known as an oyster mushroom that is very popular because of its high nutritional value and pharmaceutical component. The aim of this research was to study the antioxidant and antibacterial activity of exopolysaccharides from P. ostreatus grown on liquid medium.The P. ostreatus was grown on Mushroom Complete Medium (MCM) containing various types of Carbon (C) and Nitrogen (N) sources, i.e glucose, lactose, amylose and sucrose as a Carbon sources and yeast extract, polypeptone, NH4Cl, and NH4NO3 as a Nitrogen sources. The results showed that sucrose and yeast extract were the best source of Carbon and Nitrogen that produced 208 and 100 mg/L of exopolysaccharides. The exopolysaccharide exhibited antimicrobial activity against Bacillus subtilis and Escherichiacoli. However, it did not have antimicrobial activity against Saccharomyces cerevisiae. In addition, the exopolysaccharide indicated to have an antioxidant activity.